2014
DOI: 10.1111/apa.12576
|View full text |Cite
|
Sign up to set email alerts
|

Animal protein intake at 12 months is associated with growth factors at the age of six

Abstract: High animal protein intake in infancy, but not vegetable protein intake, was associated with accelerated growth and higher BMI in childhood. Dairy protein intake in infancy may be positively associated with linear growth and also with IGF-1 in six-year-old girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 30 publications
(45 reference statements)
3
38
0
Order By: Relevance
“…Similar to our results, others have failed to find any significant relationships between red meat consumption and abdominal obesity . In addition, some studies claimed that animal proteins (such as dairy and meat proteins) are not predictors of BMI at 6 years …”
Section: Discussionsupporting
confidence: 89%
“…Similar to our results, others have failed to find any significant relationships between red meat consumption and abdominal obesity . In addition, some studies claimed that animal proteins (such as dairy and meat proteins) are not predictors of BMI at 6 years …”
Section: Discussionsupporting
confidence: 89%
“…26 The annual intake of vegetable food protein in European infants is in general less than that of animal food protein. 27 Lastly, a single grain of grass pollen contains on average only 2.3 pg (one millionth of a microgram) of Phl p 5, and in Germany approximately 2000 grass pollen grains are cumulatively dispersed per cubic meter per year. 28 This suggests that a German child inhales no more than a few micrograms of Phl p 5 per year.…”
Section: Effect Of Exposure On Igg Responsesmentioning
confidence: 99%
“…A cross-sectional analysis of healthy Danish children found that height was significantly associated with total protein, animal protein and milk intake, but not with either meat or vegetable protein intake [13]. A study in Iceland found that healthy toddlers with the highest quartile of animal protein consumption, compared with the lowest quartile, had greater weight, height and BMI at 12 months old [14]. A 20-year prospective cohort study in a healthy Danish population found that pregnant women who consumed high amounts of milk (>150 mL/day) produced offspring with significantly greater adult height than mothers who consumed less milk (<150 mL/day) [15].…”
Section: Does Evidence Suggest An Additional Growth Benefit From Asf?mentioning
confidence: 99%
“…Regular consumption of milk or animal protein, but not meat, has been positively associated with increased serum IGF-1 [13]. A recent study also associated dairy protein intake with serum IGF-1 levels in six-year-old girls [14]; however, seven-day supplementation of casein, but not whey, increased serum IGF-1 in healthy Danish boys [45]. Without the synergistic effect of all milk components, whey’s individual effect on IGF-1 and subsequent growth remains unsupported [3,43].…”
Section: Additional Justification For the Inclusion Of Asf In Fbfmentioning
confidence: 99%